Analysis Determinants of Firm Value Going Public - Santoso, Aprih; Susilowati, Teti (Jurnal Manajemen, 2023)
The aim of this research is to analyze GGC, company size, profitability affect firm value with CSR as moderation. The population is Food and Beverage Industry Sub-Sector Companies Registered in the 2016 – 2022 using purposive sampling, 27 companies were obtained as research samples. The data were processed by multiple regression analysis with the help of the IBM SPSS Statistics 26. The results showed: 1) GGC, size, profitability had a positive and significant effect on firm value. 2) CSR is able to moderate the influence of GGC, size, profitability on firm value.